2013
DOI: 10.1002/ange.201301694
|View full text |Cite
|
Sign up to set email alerts
|

Regioselektive Metallierungen von Pyrimidinen und Pyrazinen mit frustrierten Lewis‐Paaren aus BF3⋅OEt2 und sterisch gehinderten Mg‐ und Zn‐Amidbasen

Abstract: Die Funktionalisierung von Diazinen ist von großer Bedeutung, da diese N-Heterocyclen in zahlreichen Naturstoffen sowie pharmazeutischen und agrochemischen Wirkstoffen vorkommen. [1] Außerdem finden sie interessante Anwendungen in der Materialwissenschaft und der Polymerchemie. [2] Die dirigierte Metallierung und weitere Funktionalisierung dieser elektronenarmen N-Heterocyclen kann mittels "at"-Basen [3] und in einigen Fällen auch mit Lithiumbasen [4] erreicht werden. Jedoch sind wegen der geringen Stabilitä… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Recently, the bis(silyl)methyl moiety has also been used for Wittig rearrangements and Prins cyclization 7. Also, we have shown that the pyrazine scaffold can be fully functionalized starting from a BTSM‐substituted pyrazine8 by using the magnesium base TMP 2 Mg ⋅ 2 LiCl ( 1 ; TMP=2,2,6,6‐tetramethylpiperidyl) 9. Herein, we report a simple way to introduce the BTSM substituent onto an aromatic system by using a Kumada–Corriu cross‐coupling reaction10 between (Me 3 Si) 2 CHMgBr ⋅ LiCl ( 2 )11 and various aryl bromides.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the bis(silyl)methyl moiety has also been used for Wittig rearrangements and Prins cyclization 7. Also, we have shown that the pyrazine scaffold can be fully functionalized starting from a BTSM‐substituted pyrazine8 by using the magnesium base TMP 2 Mg ⋅ 2 LiCl ( 1 ; TMP=2,2,6,6‐tetramethylpiperidyl) 9. Herein, we report a simple way to introduce the BTSM substituent onto an aromatic system by using a Kumada–Corriu cross‐coupling reaction10 between (Me 3 Si) 2 CHMgBr ⋅ LiCl ( 2 )11 and various aryl bromides.…”
Section: Methodsmentioning
confidence: 99%
“…The bis(trimethylsilyl)methyl group (BTSM) [1] pioneered by Snieckus [2] has been used for the efficient regioselective metalation of aromatic substrates, [3] as wella sf or that of af ew heterocycles, such as pyrazines. [4] Additionally,t he BTSMg roup has recently found an umber of applications in organic synthesis [5] due to its unique synthetic features (steric hindrance combined with facile transformation). Herein, we report the preparation of various BTSM-substituted heterocyclesa sw ell as their regioselective metalation [6] andf urther functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their ubiquity in the biological sciences, pyrimidine derivatives are also common building blocks in many functional materials such as supramolecular assemblies, non-linear optics and organic electronics. [2] The ring C-H metalation of pyrimidines offers a direct means to further functionalize these systems, [3] and this has been successfully implemented at C2, [4] C4, [5] and C5. [6] However, ring metalation requires strong bases and often leads to low yields of products due to the propensity of these intermediates to undergo dimerization.…”
mentioning
confidence: 99%